Histiocytosis Otomastoiditis X: About a clinical case - Von-Haff, Luzbel (2021)
Langerhans cell histiocytosis (LCH) or histiocytosis X refers to a group of diseases that are characterized by the clonal proliferation of histiocyte with characteristics similar to Langerhans cells, which affect different organs of the human body, including the temporal bone. The present work describes the clinical case of a 42-year-old patient admitted to surgery for acute otomastoiditis on the right. Axial Computed Tomography (CAT) revealed petromastoid osteolytic lesions, dehiscence of the lateral sinus and external semicircular canal and a solution of continuity of the tympanic tegmen, but without infiltration of neurological structures. The diagnosis of temporal bone LCH was confirmed with histopathological and immunohistochemical exams. Depending on the type of injury, there are different therapeutic modalities for LCL of the temporal bone that include surgery, chemotherapy, radiotherapy and even corticotherapy. In this case, the patient underwent a mastoidectomy on the right, followed by corticosteroid therapy (dexamethasone) and chemotherapy (vinblastine). Up to the current date, the patient has shown no signs of disease recurrence. However, is kept on periodic surveillance to detect any clinical manifestations.